Persian interventions - Hyland, John O., 1977- (Baltimore)
[xii], 257 sayfa
Keywords: “In this book, Hyland examines the international relations of the First Persian Empire (the Achaemenid Empire) as a case study in ancient imperialism. He focuses in particular on Persian's relations with the Greek city-states and its diplomatic influence over Athens and Sparta. Previous studies have emphasized the ways in which Persia sought to protect its borders by playing the often warring Athens and Sparta off each other, prolonging their conflicts through limited aid and shifts of alliance. Hyland proposes a new model, employing Persian ideological texts and economic documents to contextualize the Greek narrative framework, that demonstrates that Persian Kings were less interested in control of the Ionian region where Greece bordered the empire than in displays of universal power through the acquisition of Athens or Sparta as client states. On the other hand, the establishment of “Pax Persica“ beyond the Aegean was delayed by Persian efforts to limit the interventions' expense, and missteps in dealing with fractious Greek allies. This reevaluation of Persia's Greek relations marks an important contribution to scholarship on the Achaemenid empire and Greek history, and has value for the broader study of imperialism in the ancient world.“ --